Praktik Ghibah Dalam Grup WhatsApp Keluarga Dalam Perspektif Hukum Islam - Salma Salsabila; Jihan Salsabila Najma Sari; Reza Fitri Ananda; Lina Kushidayati (Yayasan Dar Arrisyah Indonesia, 2025)
The proliferation of digital communication platforms, particularly family WhatsApp groups, has facilitated interpersonal connectivity while simultaneously introducing ethical dilemmas such as ghibah (backbiting). This study investigates the manifestation of ghibah within family WhatsApp groups from the perspective of Islamic law. Employing a qualitative descriptive methodology through literature review and content analysis, the research draws upon primary Islamic legal sources—including the Qur’an, Hadith, scholarly interpretations, and fatwas issued by institutions like the Indonesian Ulema Council (MUI). The findings reveal that despite the private and informal nature of family WhatsApp groups, ghibah remains categorically prohibited and is considered a major sin in Islam. It typically manifests through behaviors such as criticizing absent members, disseminating private information without consent, or making demeaning remarks masked as humor. These actions not only compromise individual dignity but also jeopardize familial harmony and trust. The study emphasizes that digital media do not exempt individuals from adhering to Islamic ethical standards. The enduring nature of digital communication exacerbates the repercussions of ghibah, thus underscoring the necessity of digital literacy grounded in Islamic ethics. This research contributes to the development of ethical guidelines for digital conduct within familial contexts and calls for the reinforcement of Islamic values in private online interactions.